ADMINISTRATION OF PREOPERATIVE SUBMUCOSAL DEXAMETHASONE IN THIRD MOLAR SURGERY: A PROGRESSION TOWARDS ENHANCING QUALITY OF LIFE. - Raham Zaman; Nazish; Saif Ullah; Zubair Nasir; Akif Mahmud; Tehmina Naushin (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: To determine the efficacy of pre-operative submucosal administration of dexamethasone in surgery of impacted third molar (M3) teeth.Methodology: Prospective comparative study was conducted at Dental Teaching hospital, from April 2024 to October 2024. A total 130 patients were enrolled in study and divided into two groups by simple randomization method. Group A was control group injected placebo and group B was case group injected 4mg dexamethasone immediately after induction of anesthesia through submucosal route. Efficacy was measured in terms of reduction in trismus, pain and inflammation in post-operative time. SPSS version 26 was used for data entry and analysis of variables.Results: The mean pain score in Group A was 28.74 ± 5.21 compared with 22.56 ± 4.02 in Group B (p < 0.001). Mean swelling was 5.01 ± 1.35 mm in Group A and 3.42 ± 0.88 mm in Group B (p < 0.001). Mean trismus measured 24.89 ± 4.10 mm in Group A and 19.78 ± 2.91 mm in Group B, with Group B showing significantly less trismus (p < 0.001Conclusion: Administering 4mg of dexamethasone through the submucosal route prior to mandibular third molar surgery can effectively reduce post-operative pain, swelling, and trismus.